LAYANAN HOME CARE DENGAN SENAM LANSIA DALAM MEMPERTAHANKAN KEBUGARAN FISIK PADA LANSIA : LAYANAN HOME CARE DENGAN SENAM LANSIA DALAM MEMPERTAHANKAN KEBUGARAN FISIK PADA LANSIA - Siti Komariyah; Lely Khulafa’ur Rosidah; Widya Kusumawati; Susiani Endarwati (JCS, 2023)
The increasing number of elderly people accompanied by the problems faced by the elderly in the aging process means that the elderly need services from various parties. Home care services are a form of assistance and social care services for the elderly in the family environment/at home as a form of attention to the elderly by prioritizing the role of family-based communities. One thing that can be done in elderly home care services is elderly exercise. Elderly exercise done regularly can prevent functional loss caused by cardiovascular disease, and another benefit of elderly exercise is that it can reduce weight and strengthen the heart muscles. Therefore, this service aims to provide Home Care Services with Elderly Exercise in Maintaining Physical Fitness for the Elderly in RW 005, Campurejo Village, Mojoroto District, Kediri City. After participating in this activity. Community service activities are carried out using pre-test, intervention and post-test methods. The results show that the elderly exercise carried out in this service activity is very beneficial for the physical fitness of the elderly (blood pressure) in RW 005, Campurejo Village, Mojoroto District, Kediri City.